Navigating mixed connective tissue disease in pregnancy: a rare case report - Nannaware, Dipika; Kamath , Anusha; Gangane, Neha; Yadav, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Autoimmune connective tissue diseases (CTDs) in pregnancy present a complex interplay between maternal health and fetal outcomes. While historically discouraged due to potential complications, proper preconception counselling and disease control offer the prospect of safe pregnancies. This case report focuses on mixed connective tissue disease (MCTD), a rare condition combining features of SLE, systemic sclerosis, rheumatoid arthritis, and polymyositis, presenting during pregnancy. A 29-year-old woman, gravida 2, para 1, with a history of rheumatoid arthritis, was referred at 31+4 weeks with a deranged coagulation profile, fetal growth restriction (FGR), and oligohydramnios. Extensive laboratory and imaging investigations confirmed MCTD diagnosis. Treatment involved LMWH, aspirin, hydroxychloroquine, and prednisolone. Comprehensive monitoring and multidisciplinary care were maintained throughout. Despite initial improvement, the patient faced complications at 35+3 weeks, leading to an emergency caesarean section at 36 weeks due to preterm FGR, oligohydramnios, and breech presentation. A male infant weighing 2.1 kgs was delivered, requiring neonatal intensive care due to prematurity and respiratory distress. Postoperatively, the mother resumed medication and was discharged with her baby. This case highlights successful MCTD management during pregnancy through meticulous monitoring and a multidisciplinary approach. The risk of complications necessitates informed preconception counselling, emphasizing the importance of disease remission, close surveillance, and prompt intervention in disease relapse. Comprehensive care, including medications and careful planning, contributes to improved maternal and neonatal outcomes in this rare and challenging scenario.